Kilfenora Cathedral, north wall, tomb niche, tracery bar - O'Donovan, Danielle (My University, 2008)
Tracery bar comprising: frontal central fillet flanked by sunk chamfer, right-angled rebate and sunk chamfer. The rear of the bar is square.
Tomb niche
Keywords: Architecture, Gothic -- Ireland; Funerary monuments; Kilfenora (Clare, Ireland); Tracery (Architecture); Late Medieval; bar tracery; moldings, hollow